PECULIARITIES OF THE DEVELOPMENT OF THE AMERICAN AND CHINESE LIGHT INDUSTRY MARKETS: A COMPARATIVE ASPECT - Касумов, Теймур А. (Journal of Strategic Economic Research, 2025)
In the current conditions of economic growth and increased competition, the light industry is becoming one of the leading industries of any country. The purpose of the article is to compare the US and Chinese light industry markets, their differences, advantages and disadvantages, as well as possible future development prospects. The article analyzes the main problems faced by the modern light industry market in China and the United States and possible ways to solve them. The study used observation and comparison methods, which revealed that the relationship between the US and Chinese markets is becoming an important factor influencing the future of the light industry, forming new business models and consumer preferences, as well as methods of economic and statistical analysis, induction and deduction. The study found that the US apparel industry was significantly affected by the crisis of the 2000s, and that China, with its strong production base and competitive prices, continues to dominate the production of textile and apparel products, and the flexibility of Chinese factories allows them to quickly adapt to consumer demands and constantly changing global fashion trends. The study showed that the US market is seeing a growing interest in sustainable and environmentally friendly production, which opens up new opportunities for local brands, and that US companies are increasingly investing in innovative technologies and practices. It was found that on the economic front, in 2023, the apparel industry in both countries studied experienced historic inflationary pressures, a severe global slowdown, weak consumer demand, and a glut of retail inventory, resulting in low demand for future textile orders, as well, as production cuts. It was found that the effects also extend beyond the US borders to the partners participating in US free trade agreements, which, together with US textile producers, form an integrated vertical chain of joint production of textiles and apparel and are a counterweight to production in Asia. The practical significance of the results of this study is that they make it possible to identify the main factors that negatively affect the development of the US and Chinese light industry markets and to build a strategy for improving these problems with minimal losses.